COVID-19 mRNA vaccination leading to CNS inflammation: a case series - Khayat-Khoei, Mahsa; Bhattacharyya, Shamik; Katz, Joshua; Harrison, Daniel; Tauhid, Shahamat; Bruso, Penny; Houtchens, Maria K.; Edwards, Keith R.; Bakshi, Rohit (Journal of neurology, 2022)
The availability of vaccines against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), provides hope towards mitigation of the coronavirus disease 2019 (COVID-19) pandemic. Vaccine safety and efficacy has not been established in individuals with chronic autoimmune diseases such as multiple sclerosis (MS). Anecdotal reports suggest that the vaccines may be associated with brain, spinal cord, peripheral nervous system, and cardiac inflammation. Based on the high morbidity and unpredictable course of COVID-19, and the need to achieve herd immunity, vaccination has been recommended for patients with MS. We report clinical and MRI features of seven individuals who received the Moderna ( n = 3) or Pfizer ( n = 4) SARS-CoV-2 mRNA vaccines. Within one to 21 days of either the first ( n = 2) or second ( n = 5) vaccine dose, these patients developed neurologic symptoms and MRI findings consistent with active CNS demyelination of the optic nerve, brain, and/or spinal cord. Symptoms included visual loss, dysmetria, gait instability, paresthesias, sphincter disturbance, and limb weakness. Age ranged from 24 to 64 (mean 39.1) years; five were woman (71.4%). The final diagnosis was exacerbation of known stable MS ( n = 4, two were receiving disease-modifying therapy at the time of vaccination), new onset MS ( n = 2), or new onset neuromyelitis optica ( n = 1). All responded to corticosteroid ( n = 7) or plasma exchange ( n = 1) therapy, with five returning to baseline and two approaching baseline. Large prospective studies are required to further investigate any possible relationship between COVID-19 vaccines and acute CNS demyelination.